Fragmented landscapes of water supply in suburban Hanoi. (March 2017) - Wright-Contreras, Lucía; March, Hug; Schramm, Sophie
Abstract: Facing the challenges of city planning in the frame of rapid urbanization in the Global South, this study addresses the relationship between the urban development of Hanoi, Vietnam, and water supply including users' perception of water accessibility and satisfaction of coverage, quality, and cost. Because sociospatial disparities are particularly pronounced in suburban areas, these spaces epitomize unequal water access and uneven water quality. Based on the premise that (sub)urban water flows embody and mirror development dynamics and urbanization patterns, the objective is to analyze access to water splintered within the suburban typologies of Hanoi. We analyze the current state of domestic water availability and quality throughout suburban areas and specifically between a new urban area and a periurban village in Hanoi. Through the debates of splintering urbanism and periurban water supply, this paper discusses the differences in water service provision in suburban Hanoi. At the same time, the article considers suburban areas as spaces which reflect a broader spectrum of water supply solutions. Lastly, it informs on how to alleviate the pressure of the increasing demand of water in urbanizing areas by supporting sustainable urban water cycles to improve distributional justice and social equity. Graphical abstract: Highlights: New urban areas and periurban villages display unequal access to water. 100 surveys show access and satisfaction of coverage, quality and cost of water. Households also rely on water from private vendors and privately-owned wells. Groundwater tests display up to 90× standard of Fe, 2× of NH4, and 30× of As. Specific (sub)urban typologies condition access to safe water sources.